2013
DOI: 10.1128/genomea.00182-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Human Adenovirus Type 7 Associated with Fatal Infant Pneumonia

Abstract: The Chinese human adenovirus 7 (HAdV7) 0901HZ/ShX/CHN/2009 was isolated from the hydrothorax fluid of an infant with fatal pneumonia in Shaanxi, China, in 2009. Comparison of the entire genome with the genomes of the other 10 strains of HAdV7 from GenBank revealed homologies of 89.9 to 99.9%, with geographic polymorphism among HAdV-7 field strains circulating in mainland China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…all of these seven strains are identified as HAdV-7d (Fig. 3), evidenced by the REA patterns and identical with the first reported HAdV-7d333435, as well as with the re-emergent HAdV-7d strains DG01_2011 and 0901HZ/ShX/20091715.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…all of these seven strains are identified as HAdV-7d (Fig. 3), evidenced by the REA patterns and identical with the first reported HAdV-7d333435, as well as with the re-emergent HAdV-7d strains DG01_2011 and 0901HZ/ShX/20091715.…”
Section: Resultssupporting
confidence: 75%
“…The further genome pairwise alignments indicated that the genome sequences of the 2 isolates (IP04_2011 and IP06_2012) were 100% identical with each other as well as with the previous HAdV-7 strain 0901HZ/ShX/2009, which was associated with the fatal pneumonia in an ARD outbreak in the Shaanxi Province of China in 2009715. The genome sequence identities between both isolates and the other five isolates were extremely high (more than 99.98%).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Strain HAdV_7_309-1B displayed one substitution at position 1228 of the hexon gene, which was a silent mutation. The strains identified in this report are closely related to the predominant HAdV7 isolates reported in China in recent years (12).…”
mentioning
confidence: 66%
“…HAdV7 transmission generally occurs through respiratory droplets and close contact, which can lead to rapid and wide-spread infection. Large community and regional outbreaks of acute respiratory disease with an increased incidence of severe and fatal outcomes caused by HAdV7 have been described in Europe and Asia (7,12,16,17). Thus, control of HAdV7 spread is crucial.…”
mentioning
confidence: 99%